2013
DOI: 10.1128/jb.00188-13
|View full text |Cite
|
Sign up to set email alerts
|

The δ Subunit of RNA Polymerase Is Required for Rapid Changes in Gene Expression and Competitive Fitness of the Cell

Abstract: dRNA polymerase (RNAP) is an extensively studied multisubunit enzyme required for transcription of DNA into RNA, yet the ␦ subunit of RNAP remains an enigmatic protein whose physiological roles have not been fully elucidated. Here, we identify a novel, so far unrecognized function of ␦ from Bacillus subtilis. We demonstrate that ␦ affects the regulation of RNAP by the concentration of the initiating nucleoside triphosphate ([iNTP]), an important mechanism crucial for rapid changes in gene expression in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 54 publications
(50 reference statements)
2
58
1
Order By: Relevance
“…1F). We note that this result contradicts the previous observation by Rabatinová et al (12). The above observations that (i) ␦ binds to RNAP core but fails to induce core-mediated transcription and (ii) ␦ does not show any affinity toward RNAP holo but requires RNAP holo for its function suggested that ␦ may function as a transcriptional regulator.…”
Section: ␦ Has No Effect On Rnap Core-mediated Transcription But Enhacontrasting
confidence: 57%
“…1F). We note that this result contradicts the previous observation by Rabatinová et al (12). The above observations that (i) ␦ binds to RNAP core but fails to induce core-mediated transcription and (ii) ␦ does not show any affinity toward RNAP holo but requires RNAP holo for its function suggested that ␦ may function as a transcriptional regulator.…”
Section: ␦ Has No Effect On Rnap Core-mediated Transcription But Enhacontrasting
confidence: 57%
“…While the stronger of these two promoters was largely unaffected by RpoE, the weaker promoter showed significantly decreased expression in the presence of this factor. In order to explain the effect of RpoE on promoter selection, Rabatinova et al (8) investigated the role of initiating nucleotide triphosphate (iNTP) recognition by RNAP and RNAPRpoE complexes. iNTP is required to stabilize open complex formation and therefore to initiate transcription.…”
mentioning
confidence: 99%
“…As with ␦ and , ε is not essential for viability and, despite much work, the functional role of the ␦ and subunits is only now being uncovered (2,4,49). No change in the transcriptome of B. subtilis could be detected on deletion of ε or any effect of ε in in vitro transcription assays, and additional studies are needed to fully elucidate its functional role in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In the model Gram-positive organism Bacillus subtilis, core RNAP has the subunit composition ␣ 2 ␤␤=␦ 1 2 (2). The ␦ subunit is encoded by the gene rpoE and is involved in RNAP promoter specificity and recycling (2)(3)(4). The ␦ subunit appears to be conserved across the Gram-positive bacteria, and despite a high cellular abundance and documented roles in gene expression, deletion strains do not exhibit a strong phenotype (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation